The origin and evolution of r- and s-process elements in the Milky Way stellar disk (corrigendum) - Battistini, Chiara; Bensby, Thomas (Astronomy and astrophysics, 2017)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics